Statesʼ rights and American federalism : a documentary history - Drake, Frederick D., 1947-; Nelson, Lynn R., 1946- (Primary documents in American history and contemporary issues., 1999)
Traces the history and development of issues surrounding the debate over states' rights versus federalism in America through primary documents, including court cases, opinion pieces, and speeches.